PEDAGOGIC IN POST-TRUTH DEMOCRACY IN INDONESIA - Hakim, Raafi Fauzia; Triatna, Cepi (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2022)
Indonesia is a country with Pancasila ideology which becomes fundamentally philosophical. Advances in the field of information technology in the era of industry 4.0 and society 5.0 seem to drown out the existence and essence of philosophy and pedagogy. This era is dominated by the role of technology where computers are increasingly intelligent. In the Ancient Greece era pedagogic was a slave who supervised and monitored the academic development of the children who attend school. Human tendencies in the post-truth age are characterized by the difficulty of distinguishing where scientific facts see flash flood conditions in the digital world, lies feel like facts that threaten electoral democracy. Education Administration is a science with a core science in the form of leadership, administration, policy analysis, supervision, and pedagogy. In the context of the post-truth problem, namely by formulating strategies in the form of influence on human reality because post-truth lives in virtual reality, replying to flood the digital world full of post-truth with educational content. Post-truth is a phenomenon that occurs when personal beliefs and emotions take precedence over facts. This study aims to suggest alternative solutions using philosophy and pedagogy to resolve the post-truth problem from the study literature. Â The conclusion of this research provides a suggestion to overcome and protect society in the post-truth era using philosophy and pedagogy perspective and increase trust in the Indonesian Armed Forces (TNI), Indonesian Police (Polri) Teachers, and lecturers as the shield of Indonesia.Â